The Role of the Vitamin D Receptor in Aging Skeletal Muscle and Inflammatory Response. - Pojednic, Rachele. (2017)
Abstract: Growing evidence suggests a strong and direct effect of vitamin D on skeletal muscle. Observational studies demonstrate a positive association between serum 25-hydroxyvitamin D (25OHD) concentration and muscle strength and function in older adults. In randomized controlled trials, vitamin D supplementation in older adults increased muscle strength and balance and reduced the risk of falls. The effects of vitamin D on aging muscle may be mediated by its receptor (VDR). VDR is expressed in human skeletal muscle and when bound to the active vitamin D metabolite, 1,25-dihydroxyvitamin-D3 (1,25(OH)2D3), it regulates expression of genes that affect muscle cell differentiation and contractility. At present, data on the relationship between 25OHD and VDR expression in human skeletal muscle are limited. In Part 1 of this dissertation, we conducted three studies to examine the effect of various metabolites of vitamin D on human skeletal muscle. These studies examined 1) the effect of increasing concentrations of 1,25-dihydroxyvitamin D3 (1,25OH2D3) on VDR gene expression in human primary myoblasts, 2) the association between serum 25-hydroxyvitamin D (25OHD) concentration and VDR protein concentration in muscle of older adults, and 3) the effect of 16-week supplementation with vitamin D3 on VDR gene expression in muscle of older women. We found that increasing 1,25OH2D3 concentration in human primary cell myoblasts significantly increased VDR mRNA expression compared to controls. In older mobility-limited adults, serum 25OHD was positively associated with VDR protein concentration. After 16 weeks of vitamin D3 supplementation, VDR mRNA expression was significantly greater compared to placebo in muscle samples of older women. In Part 2 of this dissertation, we examined the role of vitamin D in skeletal muscle inflammation using two models. First, we assessed the cross sectional associations between 25OHD and/or VDR concentration with intramuscular inflammatory markers (IL-6 and TNFa) and related signaling pathways (NFkB and p38 MAPK phosphorylation). Second we investigated the longitudinal affects of 16 weeks of vitamin D3 supplementation on alterations in skeletal muscle inflammatory markers (IL-6 and TNFa). We found that intramuscular VDR protein concentration was positively associated with intramuscular IL-6 gene expression but negatively associated with intramuscular IL-6 protein concentration in older mobility-limited adults. However, intramuscular IL-6 gene expression was not altered after 16 weeks of vitamin D3 supplementation in older mobility-limited women. Neither intramuscular VDR nor serum 25OHD was associated with intramuscular TNFa. In conclusion, these data suggest 1) a direct relationship between 1,25OH2D3 and 25OHD concentrations with human intramuscular VDR mRNA and protein concentration and 2) a subsequent association with intramuscular IL-6. Our findings generate important hypotheses on the role of vitamin D in skeletal muscle; however, larger randomized trials are needed to confirm our findings.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Roger Fielding.; Committee: Bess Dawson-Hughes, Alice Lichtenstein, and Lisa Ceglia.; Keywords: Nutrition, Physiology, and Aging.